Oral health related quality of life (OHRQOL) among residents in a care home in Terengganu, Malaysia; A cross sectional study - Mohd, Farah Natashah; Said, Abdul Hadi; Sukmasari, Susi; Ismail, Nor Iziana; Musa, Nor Mulyani (SciDoc Publishers, 2020)
Objective: This study aimed to assess the oral health related quality of life (OHRQOL) among residents living in a care home in Terengganu, Malaysia and its associated factors. Method: A cross sectional study using universal sampling to assess the OHRQOL among residents in a care home in Tereng- ganu state was done from July to August 2018. The OHRQOL was assessed using a validatedshort Oral Health Impact Profile (S-OHIP) Malay version questionnaire. Association between OHRQOL and sociodemographic profile as well as their oral health status was also analysed. Results: The mean total S-OHIP score was 6.28 ±5.72. The most commonly reported S-OHIP dimension was psychological discomfort due to food getting stuck with a mean score of 1.33 ±1.64. On the other hand, avoided going out was the least impact with a mean score of 0.27± 0.94. Those who were able to ambulate had better OHRQOL while those who perceived they need dental treatments have poorer OHRQOL. Surprisingly, those with underlying stroke have lower S-OHIP score in- dicates better OHRQOL compared to those without stroke. Furthermore, there was no significant association found between OHRQOL and their oral health status. Conclusion: The S-OHIP score of the participants was low compared to the other local studies among other population indicating that they have good OHRQOL. Inability to ambulate and self-perceived need for dental treatments were shown to give more impact towards their OHRQOL. Despite the finding that the impact was low among the residents, it is important to make sure they receive continuous oral care to maximise their OHRQOL as well as their overall quality of life.